Ekonomi Kreatif: Upaya Menjadikan Bahasa Bali Masuk dalam Kancah Entrepreneurship - I Made Suweta (Purwadita : Jurnal Agama dan Budaya, 2020)
The preservation of the Balinese language cannot only preserve the existence of Balinese language, script, and literature. In order to be sustainably maximized, Balinese should also be empowered to take a role in economic life. There must be creativity of human ideas that support the Balinese language in order to exist in entrepreneurship, as a creative economic development. Therefore, the writing will discuss issues relating to the creative economy and efforts to develop Balinese in the creative economy. Economic activities, which in their development are called creative economics, penetrate into various aspects of life related to the needs of human life, including also relating to speaking in Balinese. The existence of Balinese in the development of the creative economy that is developing in various fields, namely: crafts (by processing palm leaves written in Balinese script); fashion (by using a T-Shirt that reads Balinese or Latin); music (through Balinese pop songs); Performing arts (through Cenk Blonk puppet show); (by utilizing social media, the Balinese language is introduced to the public through creative and interesting videos).  Keywords: creative economy, entrepreneurship, Balinese language